Enhance Features in URDU.KON-TB - Munir, Saima (International Multidisciplinary Research Journal, 2019)
In this paper, we enhance features are the head & dependent relationship and functional tagset is marked by dependency grammar rules in URDU.KON-TB for increase the accuracy. The SSP and SSS tagset are using [1]. In this way, we conduct one experiment with six different feature models using MaltParser. First we check converted ability of URDU.KON-TB in domain of dependency parsing through conversion, so that’s why we need to proposed formula and defined rules.